Exploring the clinical utility of DPP-IV and SGLT2 inhibitors in papillary thyroid cancer: a literature review - Buczyńska, Angelika; Kościuszko, Maria; Krętowski, Adam Jacek; Popławska-Kita, Anna (Frontiers in Pharmacology, 2024)
In the realm of clinical management, Papillary Thyroid Cancer (PTC) stands out as a prevalent thyroid malignancy, characterized by significant metabolic challenges, particularly in the context of carbohydrate metabolism. Recent studies have unveiled promising applications of Dipeptidyl Peptidase-IV (DPP-IV) and Sodium-Glucose Cotransporter 2 (SGLT2) inhibitors, which are conventionally employed in the treatment of type 2 diabetes mellitus (T2DM), as potential adjuncts in anticancer therapy. DPP-IV and SGLT2 inhibitors can be imply to counteract the Warburg effect in cancer, with a specific focus on PTC, owing to their potential metabolic advantages and their influence on the tumor microenvironment, achieved by imposing restrictions on glucose accessibility. Consequently, a comprehensive review has been undertaken, involving meticulous examination of the existing body of evidence pertaining to the utilization of DPP-IV and SGLT2 inhibitors in the context of PTC. The mechanisms of action inherent to these inhibitors have been thoroughly explored, drawing upon insights derived from preclinical investigations. Furthermore, this review initiates discussions concerning the implications for future research directions and the formulation of innovative therapeutic strategies for PTC. As the intricate interplay between carbohydrate metabolism, the Warburg effect, and cancer progression garners increasing attention, attaining a comprehensive understanding of the roles played by DPP-IV and SGLT2 inhibitors in PTC management may serve as the cornerstone for novel approaches aimed at enhancing patient care and broadening the spectrum of available therapeutic modalities.